2022
DOI: 10.3389/fmicb.2022.842414
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Purpose Approach to the Mechanisms of Action of Two Biocides (Benzalkonium Chloride and Dibromonitrilopropionamide): Discussion of Pseudomonas fluorescens’ Viability and Death

Abstract: Biocides are widely used in water treatment for microbiological control. The rise of antimicrobial resistance and the need to assure properly managed water systems require a better understanding of the mechanisms of action of biocides and of their impact on cell’s viability as a function of dosage concentrations. The present work addresses these two aspects regarding the biocides benzalkonium chloride (BAC) and dibromonitrilopropionamide (DBNPA)—two biocides commonly found in the water treatment industry. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…The definition of MBC is the lowest biocidal concentration able to kill 99.9% of the initial bacterial population [ 24 ]. Therefore, when cells were first exposed to the MBC and higher concentrations [ 23 ], no CFU/mL counts were observed. This means that, for both biocides, cells were able to significantly regrow when stress conditions (biocide effect) were removed, and nutritional requirements were met.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The definition of MBC is the lowest biocidal concentration able to kill 99.9% of the initial bacterial population [ 24 ]. Therefore, when cells were first exposed to the MBC and higher concentrations [ 23 ], no CFU/mL counts were observed. This means that, for both biocides, cells were able to significantly regrow when stress conditions (biocide effect) were removed, and nutritional requirements were met.…”
Section: Resultsmentioning
confidence: 99%
“…The work of Barros et al [ 23 ] discussed that BAC, due to its cationic nature, strongly interacts with bacterial cell membranes, inducing small membrane pores that allow PI entrance into the cells. The authors demonstrated that only 30 mg/L of BAC can lead to 100% of PI uptake, even though P. fluorescens remained culturable for concentrations below the MBC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main target of BAC is thought to be the bacterial cell envelope 2,7 . The general mode of action likely proceeds as follows: the cationic headgroup attaches to anionic sites on the cell surface, which possesses a net negative charge.…”
Section: Introductionmentioning
confidence: 99%